2009
DOI: 10.2353/jmoldx.2009.080079
|View full text |Cite
|
Sign up to set email alerts
|

Direct Bacterial Profiling by Matrix-Assisted Laser Desorption−Ionization Time-of-Flight Mass Spectrometry for Identification of Pathogenic Neisseria

Abstract: The present study investigates the suitability of direct bacterial profiling as a tool for the identification and subtyping of pathogenic Neisseria. The genus Neisseria includes two human pathogens , Neisseria meningitidis and Neisseria gonorrhoeae, as well as several nonpathogenic Neisseria species. Here , a matrix-assisted laser desorption/ionization time-of-flight mass spectrometry profiling protocol was optimized using a laboratory strain of E. coli DH5␣ to guarantee high quality and reproducible results. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0
7

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(85 citation statements)
references
References 29 publications
(24 reference statements)
5
73
0
7
Order By: Relevance
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…agalactiae and 72% of CNS were identified by API system. The results tabulated in the current study, supported by similar and widespread data for clinical human and veterinary microbiology (Ilina et al, 2009;Lartigue et al, 2009; Science Publications Marklein et al, 2009;Nagy et al, 2009;Barreiro et al, 2010;Dubois et al, 2010;Ilina et al, 2010;Seibold et al, 2010;Moon et al, 2013;Raemy et al, 2013), confirmed that MALDI-TOF MS contributes in the fast identification of bacteria (one day versus five to eight days for conventional identification) and consequently the chance of an earlier treatment of subclinical and clinical mastitis with suitable antimicrobial agents will be carried out. In addition, in the dairy industry, MALDITOF MS can provides a faster, cheaper and more reliable identification of microorganisms isolated from milk of animals witth clinical and subclinical mastitis.…”
Section: Discussionsupporting
confidence: 65%
“…This technique requires slight Mass Spectral (MS) ability, the utilize of uncomplicated instruments and relatively fast operator training. After comparing mass spectral identification with DNA analysis based technologies, it was found that MALDI-TOF MS requires smaller amounts of biological material and involves simpler sample preparation protocols with no initial assessment, such as Gram staining (Ilina et al, 2009;Chalupová et al, 2014;Tomazia et al, 2014). In the current study, the performance of MALDI-TOF-MS was evaluated comparing with conventional methods for bacterial screening of clinical and subclinical mastitis in dairy cows.…”
Section: Introductionmentioning
confidence: 99%
“…Anders als bei den biochemischen Testsystemen handelt es sich beim MALDI-TOF MS-System um ein offenes, bei dem die Datenbank auch vom Anwender eigenst ä ndig erweitert werden kann. Durch entsprechende Erg ä nzungen der Referenz-Spektren der Datenbanken konnte eine nahezu 100 % Identifi zierungsrate von Neisserien [11] , Clostridien [12] , Mycobakterien [13] , Salmonellen [14] , vergr ü nenden Streptokokken [15] und Helicobacter pylori [16] erreicht werden. W ä hrend das MALDI-TOF MS-System im Vergleich zu biochemischen Testsystemen im Bereich der Differenzierung von Enterobakterien, Staphylokokken und Streptokokken vergleichbar gute Ergebnisse liefert, zeigt es deutliche Vorteile bei der Differenzierung von Gram-positiven St ä bchen [17] , Anaerobiern und einigen Nonfermentern [18,19] .…”
Section: Einsatz Der Maldi-tof Massenspektrometrie In Der Mikrobiologunclassified
“…Впервые использование масс-спектрометрии для идентификации бактерий было предложено в 1975 году [9], сейчас метод прямого MALDI -масс-спектрометрического профилирования используется многими клиническими и научными лабораториями мира для решения задач по исследованию клеточных микроорганизмов [10][11][12][13][14][15][16]. Данный подход основан на накоплении MALDI масс-спектров грубого лизата клеток исследуемого микроорганизма и последующим сопоставлении их с аналогичными масс-спектрами, хранящимися в базах данных или между собой.…”
Section: Introductionunclassified